Income Distribution In Brazil 1981-1990 Parametric and Non-Parametric Approach - Cowell, Frank A.; Ferreira, Francisco H.G.; Litchfield, Julie A. (Journal of Income Distribution®, 1999)
We examine changes in the shape of the Brazilian income distribution during the “lost decade” of the 1980s, using a recently available comprehensive micro-data set. We show that income inequality increased during the decade and that average real incomes also increased. We illustrate some of the difficulties involved in modeling income distributions, particularly ones as skewed as that of Brazil, by applying kernel density estimation techniques, and examine separately the upper tail of the distribution by fitting Pareto functions. The shape of the underlying income distribution was transformed in a particularly interesting fashion during the 1980s, becoming flatter and broader throughout the decade. Inequality amongst the rich also increased during the decade with Pareto’s a falling between 1981 and 1990.